Design and analysis of a new outer-rotor permanent-magnet flux-switching machine for electric vehicle propulsion - Fei, Wei-Zhong; Shen, Jian-Xin; Wang, Can-Fei; Luk, Patrick Chi-Kwong (Cranfield University, 2011)
Purpose − The purpose of this paper is to propose a new outer-rotor permanent- magnet flux-switching machine for in-wheel electric vehicle propulsion. The paper documents both the design procedure and performance investigation of this novel machine. Design/methodology/approach − The topology and preliminary sizing equations of the outer-rotor permanent-magnet flux-switching machine are introduced. Both the number and width of rotor poles are then optimized using comprehensive two-dimensional FEA. The machine losses are particularly investigated by transient FEA for the optimal design. Findings − A outer-rotor permanent-magnet flux-switching machine, with 12 stator poles and 22 rotor poles, is most suitable for the proposed application. The analytical sizing equations are quite efficient with a suitable level of accuracy for preliminary design. The optimal rotor pole width from the FEA results is nearly 1.3 times of the original one. The efficiency of the proposed machine under rated load is relatively low, nearly 85%, as a result of significant eddy current losses in the permanent magnets, which can be effectively suppressed by implementing segmentation. The predicted outstanding performance implies that by adopting magnet segmentation the proposed machine is a leading contender for direct electric vehicle drives. Research limitations/implications − The end effects, which could be considerable in the machine with relatively short axial length, are neglected during the study. In addition, due to the high current density and deep slot, proximity losses in the winding which is not issued in this research could be significant. All the limitations mentioned above could bring corresponding errors to the results. Although the research is concentrated on the application of electric vehicle drive, the techniques can be potentially employed for other applications. Practical implications − The practical implementation of such a machine is confronted with several mechanical hurdles, especially the thermal issues which can be addressed by implementing innovative cooling system. Originality/value − The outer-rotor permanent-magnet flux- switching machines so far have not been addressed yet. This research provides designers with the technical background and another alternative for electric vehicle